Celebrity Politicians: Political Legitimacy in the 2024 Election in Indonesia - Muliani Muliani; Abdurrahman Abdurrahman; Rifaid Rifaid (Jurnal Pemerintahan dan Politik Lokal, 2026)
The phenomenon of celebrity politicians' involvement in the 2024 elections in Indonesia marks a new dynamic in the political system, which is increasingly oriented towards popularity rather than representative ability. The increasing participation of public figures from the entertainment industry reflects a paradigm shift in electoral democracy, where political legitimacy is no longer determined solely by political credibility and capacity, but by the ability to build an image and emotional closeness with the public. This study aims to analyze how celebrity politicians build and maintain political legitimacy through communication strategies and narrative construction on social media during the 2024 elections. This study uses a descriptive qualitative method based on content analysis with a thematic analysis approach processed using NVivo 12 Plus software. Data were obtained from secondary sources such as documentation, scientific literature, and online media reports. The use of NVivo made it easier for researchers to identify main themes, map communication patterns, and analyze the symbolic constructions used by celebrities in shaping public perceptions of their political legitimacy. The results show that the strengthening of the political party dimension only reached about 30%, while most celebrities were chosen because of their popularity, not their contribution to party ideology or cadre development. This condition shows that the legitimacy obtained by celebrity politicians is symbolic and temporary, oriented towards image rather than substantial capacity. The 2024 general election thus confirms the weakness of the Indonesian political system in balancing political personalization and democratic quality. Without serious reforms in political education, accountability, and party recruitment, Indonesian democracy has the potential to stagnate in terms of formal legitimacy without improvement in the quality of governance.